Analysis of the Influence of Transformational Leadership Style, Work Motivation, and Work Environment on Employee Performance with Job Satisfaction as a Mediating Variable at PT BPR Bank Jombang Perseroda - Mohamad Ilham Putra Arifin; Siti Mujanah; Ida Aju Brahma Ratih (International Journal of Economics (IJEC), 2026)
PT. BPR Bank Jombang Perseroda is one of the regional financial institutions that has a strategic role in supporting the economy of Jombang Regency. As a Regionally-Owned Enterprise (BUMD), Bank Jombang is not only profit-oriented, but also on public service and community economic empowerment. In carrying out this role, Bank Jombang faces various challenges, both internally and externally. Competition with other financial institutions such as commercial banks, cooperatives, and digital financial platforms demands innovation and improvement in the quality of human resources. Therefore, systematic managerial efforts are needed to optimize employee potential so that they can work productively and result-oriented. Employees at PT BPR Bank Jombang Perseroda show that there are still variations in the level of performance between employees, both in terms of productivity, speed of service, and quality of work, which is a phenomenon in this study. The purpose of this study is to analyze the influence of Transformational Leadership Style, work motivation, and work environment on employee performance with job satisfaction as a mediating variable at PT BPR Bank Jombang Perseroda. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The study population is employees of PT BPR Bank Jombang Perseroda. Respondents were selected using a saturated non-probability sampling method with 100 respondents. Data were analyzed using descriptive analysis and SEM-PLS analysis. The results showed that the variables of transformational leadership style, work motivation, and work environment had a positive and significant effect on employee performance through employee job satisfaction at PT BPR Bank Jombang Perseroda